Dynamics in the prevalence and clinical manifestations of acute mountain sickness of different ascent protocols during high altitudes exposure - Zhao, Caitong; Zhao, Xinyu; Ma, Yan; Liu, Yupeng; Chen, Renzheng; Sha, Lide (Frontiers in Public Health, 2024)
BackgroundLeisure, work, and sports activities that involve ascending to high altitudes (HA) are growing in popularity, yet they also pose the risk of developing acute mountain sickness (AMS). Despite the dynamic nature of AMS, its prevalence, clinical manifestations, and associated risks have still not to be comprehensively characterized.MethodsA total of 770 healthy males, ranging in age from 18 to 45 years, were included in this study. The subjects were divided into two cohorts: a fast ascent cohort (n = 424) who ascended to 3,650 m by airplane, and a slow ascent cohort (n = 346) who ascended to the same altitude by bus. Subsequently, they all further ascended to 4,400 m. AMS was diagnosed using the Lake Louise Scoring system (LLS), with either the old or new version were employed.ResultsAs diagnosed by the old LLS and new LLS, the incidence of AMS was 37.9 and 32.4% at 3650 m, respectively, which decreased to 35.7 and 32.4% after further ascending to 4,400 m in the fast ascent cohort; the incidence of AMS was 26.5 and 23.2% at 3650 m, which increased to 44.5 and 42.3% after further ascending to 4,400 m in the slow ascent cohort. Furthermore, there were noticeable disparities in the occurrence and progression of AMS-related symptoms among cohorts adhering to different ascent protocols. Specifically, fast ascent protocol posed a risk during the initial phase of the ascent, but transformed into a protective effect upon further ascent to a higher altitude.ConclusionAscent protocol emerged as the pivotal influence on the prevalence of AMS and associated manifestations, demonstrating a transition from a risk factor during initial ascent to a protective factor following further ascent to higher altitudes. These findings suggest an innovative strategy for high-altitude expeditions and work endeavors, emphasizing the importance of a strategic plan for ascending to higher altitudes.